Resin composition
By adding PMI copolymer and AAS copolymer to PC/ABS resin, the shortcomings in thermal resistance of the existing resins are solved, and high thermal resistance, good molding and coating properties of the resin combination are achieved.
Patent Information
- Application Number
- JP2021042299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-16
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-03-16
AI Technical Summary
There is room for improvement in the thermal resistance of existing PC/ABS resins.
A resin combination comprising polycarbonate resin (PC), ABS resin and styrene-N-phenyl maleimide-maleic anhydride-acrylonitrile copolymer (PMI copolymer) was used, and acrylonitrile-acrylate-styrene copolymer (AAS copolymer) was added therein.
The thermal resistance performance of the resin combination is significantly improved while maintaining good molding and coating performance.
Smart Images

Figure 0007655670000001 
Figure 0007655670000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a resin composition and a molded article obtained by molding the resin composition. [Background technology]
[0002] Alloy resin (PC / ABS resin) made of polycarbonate resin (PC resin) and styrene-acrylonitrile-butadiene resin (ABS resin) is widely used in vehicle parts, home appliances, office equipment parts, etc. because of its excellent impact resistance, heat resistance, and moldability.
[0003] Patent Document 1 discloses a resin composition containing a PC resin, an ABS resin, and a styrene-maleic anhydride copolymer. Patent Document 2 discloses a resin composition containing a rubber-reinforced vinyl resin, a polyolefin resin, and a PC resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-131867 A [Patent Document 2] JP 2019-19238 A Summary of the Invention [Problem to be solved by the invention]
[0005] Further improvement in heat resistance is required for PC / ABS resins. The present disclosure has been made in consideration of the above-mentioned circumstances, and has an object to provide a resin composition having excellent heat resistance and a molded article molded from the resin composition. The present disclosure can be realized in the following forms. [Means for solving the problem]
[0006] [1] A polycarbonate resin; ABS resin and Styrene-N-phenylmaleimide-maleic anhydride-acrylonitrile copolymer; A resin composition comprising: Effect of the Invention
[0007] The resin composition of the present disclosure has excellent heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Here, a preferred example of the present disclosure is given. [2] The content of the polycarbonate resin is 5 parts by mass or more and 95 parts by mass or less, The content of the ABS resin is 5 parts by mass or more and 95 parts by mass or less, The resin composition has a content of the styrene-N-phenylmaleimide-maleic anhydride-acrylonitrile copolymer of 1 part by mass or more and 40 parts by mass or less. [3] A resin composition comprising an acrylonitrile-acrylate-styrene copolymer. [4] A resin composition, wherein the content of the acrylonitrile-acrylic acid ester-styrene copolymer is 1 part by mass or more and 10 parts by mass or less. [5] A molded product made from a resin composition.
[0009] The present disclosure will be described in detail below. In this specification, a description using "~" for a numerical range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".
[0010] 1.Resin composition The resin composition of the present disclosure contains a polycarbonate resin, an ABS resin, and a styrene-N-phenylmaleimide-maleic anhydride-acrylonitrile copolymer (hereinafter also referred to as a "PMI copolymer").
[0011] The content of the polycarbonate resin is preferably 5 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 40 parts by mass or more, from the viewpoint of improving the heat resistance and moldability of the resin composition. The content of the polycarbonate resin is preferably 95 parts by mass or less, more preferably 85 parts by mass or less, and even more preferably 70 parts by mass or less, from the viewpoint of improving the heat resistance and moldability of the resin composition. From these viewpoints, the content of the polycarbonate resin is preferably 5 parts by mass or more and 95 parts by mass or less, more preferably 20 parts by mass or more and 85 parts by mass or less, and even more preferably 40 parts by mass or more and 70 parts by mass or less.
[0012] The content of the ABS resin is preferably 5 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 25 parts by mass or more, from the viewpoint of improving the heat resistance and moldability of the resin composition. The content of the ABS resin is preferably 95 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 40 parts by mass or less, from the viewpoint of improving the heat resistance and moldability of the resin composition. From these viewpoints, the content of the ABS resin is preferably 5 parts by mass or more and 95 parts by mass or less, more preferably 15 parts by mass or more and 70 parts by mass or less, and even more preferably 25 parts by mass or more and 40 parts by mass or less.
[0013] From the viewpoint of improving the heat resistance and moldability of the resin composition, the content of the PMI copolymer is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more. From the viewpoint of improving the heat resistance and moldability of the resin composition, the content of the PMI copolymer is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less. From these viewpoints, the content of the ABS resin is preferably 1 part by mass or more and 40 parts by mass or less, more preferably 2 parts by mass or more and 30 parts by mass or less, and even more preferably 3 parts by mass or more and 20 parts by mass or less.
[0014] The resin composition preferably contains an acrylonitrile-acrylic acid ester-styrene copolymer (hereinafter also referred to as an AAS copolymer).
[0015] 2. Polycarbonate resin The polycarbonate resin is not particularly limited. The polycarbonate resin is a polymer having a carbonate bond represented by the general formula -[-OROC(=O)-]-. R is generally a hydrocarbon, and depending on the type of divalent hydroxy compound used as a raw material, there are, for example, aromatic polycarbonates, aliphatic polycarbonates, and alicyclic polycarbonates. In addition, it may be a homopolymer consisting of one type of repeating unit, or a copolymer consisting of two or more types of repeating units. Polycarbonates using bisphenol A as a divalent hydroxy compound as a raw material are widely produced industrially and can be used preferably.
[0016] The divalent hydroxy compound may be any compound having two hydroxyl groups in the molecule, such as 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), hydroquinone, resorcinol, and other dihydroxybenzenes; ,4´-biphenol, 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl-3-methylphenyl)propane, 2,2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)methane, 1,1-bis(p-hydroxyphenyl)ethane, 2,2-bis(p-hydroxyphenyl)butane, 2,2-bis(p-hydroxyphenyl)pentane, 1,1-bis(p-hydroxyphenyl)cyclohexane, 1,1-bis(p-hydroxyphenyl)-4-isopropylcyclohexane, 1,1-bis(p-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(p -hydroxyphenyl)-1-phenylethane, 9,9-bis(p-hydroxyphenyl)fluorene, 9,9-bis(p-hydroxy-3-methylphenyl)fluorene, 4,4'-(p-phenylenediisopropylidene)bisphenol, 4,4'-(m-phenylenediisopropylidene)bisphenol, bis(p-hydroxyphenyl)oxide, bis(p-hydroxyphenyl)ketone, bis(p-hydroxyphenyl)ether, bis(p-hydroxyphenyl)ester, bis(p-hydroxyphenyl)sulfide, bis(p-hydroxy-3-methylphenyl)sulfide, bis(p-hydroxyphenyl)sulfone, bis(3,5-dibromo-4-hydroxyphenyl)sulfone, bis(p-hydroxyphenyl)sulfoxide, etc. These can be used alone or in combination of two or more.
[0017] A known method can be used to produce a polycarbonate resin, including, for example, the transesterification method (also called the melting method or melt polymerization method) in which bisphenol A and diphenyl carbonate are melted at high temperature and transesterified under reduced pressure while removing the phenol produced, the phosgene method (also called the interfacial polymerization method) in which phosgene is reacted with an aqueous caustic soda solution or aqueous suspension of bisphenol A in the presence of methylene chloride, and the pyridine method in which bisphenol A is reacted with phosgene in the presence of pyridine and methylene chloride.
[0018] The weight average molecular weight of the polycarbonate resin is preferably from 10,000 to 200,000, and more preferably from 10,000 to 100,000. The weight average molecular weight of the polycarbonate resin is a value calculated in terms of polystyrene measured by gel permeation chromatography (GPC).
[0019] 3. ABS resin The ABS resin is not particularly limited. The ABS resin is a resin containing three components, acrylonitrile, butadiene, and styrene. The ABS resin may be a copolymer, a graft copolymer, or a polymer blend in which these are mixed. There is no particular limitation on the method for producing the ABS resin, and any method such as continuous bulk polymerization, emulsion polymerization, solution polymerization, and suspension polymerization may be used.
[0020] 4.PMI copolymer The PMI copolymer is not particularly limited. The PMI copolymer is a copolymer having styrene monomer units, N-phenylmaleimide monomer units, maleic anhydride monomer units, and acrylonitrile monomer units as constituent units. The weight average molecular weight and molecular weight distribution (ratio of weight average molecular weight / number average molecular weight) of the PMI copolymer are 100,000 to 180,000 and 2.0 to 3.5, respectively. When the weight average molecular weight is less than 100,000, the mechanical properties of the resulting resin composition are insufficient, and when the molecular weight distribution exceeds 3.5, the mechanical properties and heat resistance are insufficient. When the weight average molecular weight exceeds 180,000 or the molecular weight distribution is less than 2.0, the impact strength of the resin composition is reduced, and defects such as silver spots occur in molded products.
[0021] For example, the PMI copolymer is heated at a temperature of 280°C and a shear rate of 1,000 s -1 The melt viscosity at this time is preferably 50 Pa·S to 600 Pa·S. If the melt viscosity is less than 50 Pa·S, the effect of imparting heat resistance is reduced. If the melt viscosity exceeds 600 Pa·S, the impact strength of the resin composition is reduced, and defects such as silver spots occur in molded products.
[0022] The Tg (glass transition temperature) of the PMI copolymer is preferably 140° C. to 190° C., more preferably 150° C. to 190° C. If the Tg is less than 140° C., the heat resistance imparting effect is reduced. If the Tg is more than 190° C., the impact strength of the resulting resin composition is reduced, and defects such as silver spots occur in molded products.
[0023] The constituent units of the PMI copolymer, when the total of the monomer units is taken as 100% by weight, are, from the viewpoint of improving the heat resistance and moldability of the resin composition, 30% by weight or more and 70% by weight or less of styrene monomer units, 25% by weight or more and 50% by weight or less of N-phenylmaleimide monomer units, and anhydrous Maleic AcidThe monomer unit is preferably 0.1% by weight or more and 25% by weight or less, and the acrylonitrile monomer unit is preferably 0.1% by weight or more and 40% by weight or less. From the viewpoint of improving the heat resistance and moldability of the resin composition, the constituent units of the PMI copolymer are preferably 40% by weight or more and 65% by weight or less of styrene monomer unit, 30% by weight or more and 50% by weight or less of N-phenylmaleimide monomer unit, and anhydrous styrene monomer unit. Maleic Acid More preferably, the monomer unit is 0.2% by weight or more and 10% by weight or less, and the acrylonitrile monomer unit is 0.5% by weight or more and 20% by weight or less. From the viewpoint of improving the heat resistance and moldability of the resin composition, the constituent units of the PMI copolymer are 40% by weight or more and 50% by weight or less of styrene monomer unit, 45% by weight or more and 55% by weight or less of N-phenylmaleimide monomer unit, anhydrous Maleic Acid More preferably, the monomer unit is from 0.5% by weight to 2% by weight, and the acrylonitrile monomer unit is from 2% by weight to 10% by weight.
[0024] The method for producing the PMI copolymer includes the steps of: mixing styrene, N-phenylmaleimide, and anhydrous anhydride, if necessary. Maleic Acid These monomers may be directly copolymerized with acrylonitrile which is copolymerizable with them by a known method, or anhydrous acrylonitrile may be directly copolymerized with them by a known method. Maleic Acid Alternatively, the unsaturated dicarboxylic anhydride monomer may be copolymerized with styrene and acrylonitrile copolymerizable with these monomers, and then reacted with ammonia and / or a primary amine to produce an unsaturated dicarboxylic acid imide derivative. However, the latter method of producing these copolymers, that is, the method of copolymerizing the unsaturated dicarboxylic anhydride monomer with an aromatic vinyl monomer and a vinyl monomer copolymerizable with these monomers and then imidizing, is more preferable in terms of copolymerizability and economy. In addition, primary amines used in the imidization reaction include methylamine, ethylamine, propylamine, butylamine, hexylamine, cyclohexylamine, decylamine, aniline, toluidine, naphthylamine, chlorophenylamine, dichlorophenylamine, bromophenylamine, dibromophenylamine, etc., and among these, aniline is particularly preferred.
[0025] The imidization reaction can be carried out in a solution state, a bulk state, or a suspension state using an autoclave. It is also possible to carry out the reaction in a molten state using a melt kneading device such as a screw extruder. The solvent used in the solution reaction in the imidization is arbitrary, and examples thereof include ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ethers such as tetrahydrofuran and 1,4-dioxane, aromatic hydrocarbons such as toluene and xylene, dimethylformamide, dimethyl sulfoxide, and N-methyl-2-pyrrolidone. The reaction temperature for the imidization is preferably in the range of 50°C to 350°C, and particularly preferably in the range of 100°C to 300°C.
[0026] The imidization reaction does not necessarily require the presence of a catalyst, but if a catalyst is used, tertiary amines such as trimethylamine, triethylamine, tributylamine, N,N-dimethylaniline, N,N-diethylaniline, etc. are suitable. The PMI copolymer may be obtained by any of the conventionally known methods such as continuous bulk polymerization, emulsion polymerization, solution polymerization, and suspension polymerization, or may be obtained by a combination of these polymerization methods, but is preferably obtained by a solution polymerization method.
[0027] 5.AAS copolymer The AAS copolymer is not particularly limited. The AAS copolymer is a copolymer having a vinyl cyanide monomer unit, an acrylic rubber monomer unit, and an aromatic vinyl monomer unit as constituent units. The AAS copolymer may have any other copolymerizable monomer as a constituent unit as necessary. The AAS copolymer can be obtained, for example, by a method of graft polymerizing a monomer component in the presence of an acrylic rubber. Examples of the polymerization method include continuous bulk polymerization, emulsion polymerization, solution polymerization, and suspension polymerization. The AAS copolymer may be used alone or in combination of two or more types.
[0028] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, etc., and among these, acrylonitrile is preferred. The vinyl cyanide monomer may be used alone or in combination of two or more kinds.
[0029] The acrylic rubber is preferably one having, for example, an α,β-unsaturated carboxylic acid ester as a constituent unit. The α,β-unsaturated carboxylic acid ester may be an acrylic acid ester or a methacrylic acid ester, and an acrylic acid ester is preferable. The acrylic acid ester may be ethyl acrylate, butyl acrylate, octyl acrylate, or the like. The acrylic rubber may be used alone or in combination of two or more kinds.
[0030] Examples of aromatic vinyl monomers include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, pt-butylstyrene, etc., and among these, styrene and α-methylstyrene are preferred. The aromatic vinyl monomers may be used alone or in combination of two or more kinds.
[0031] The AAS copolymer is also referred to as ASA, and is preferably a copolymer having acrylonitrile monomer units, acrylic acid ester monomer units, and styrene monomer units as constituent units.
[0032] The content of the AAS copolymer is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, from the viewpoint of improving the heat resistance and moldability of the resin composition. The content of the AAS copolymer is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less, from the viewpoint of improving the heat resistance and moldability of the resin composition. From these viewpoints, the content of the AAS copolymer is preferably 1 part by mass or more and 10 parts by mass or less, more preferably 2 parts by mass or more and 8 parts by mass or less, and even more preferably 3 parts by mass or more and 6 parts by mass or less.
[0033] The viscosity of the AAS copolymer is measured at a temperature of 240°C and a shear rate of 1,000 s -1At this time, the melt viscosity is preferably 200 Pa·S to 500 Pa·S.
[0034] The constituent units of the AAS copolymer are preferably 5% by weight or more and 35% by weight or less of acrylonitrile monomer units, 3% by weight or more and 35% by weight or less of acrylic acid ester monomer units, and 50% by weight or more and 85% by weight or less of styrene monomer units, when the total of each monomer unit is taken as 100% by weight, from the viewpoint of improving the heat resistance and moldability of the resin composition. The constituent units of the AAS copolymer are more preferably 10% by weight or more and 30% by weight or less of acrylonitrile monomer units, 10% by weight or more and 30% by weight or less of acrylic acid ester monomer units, and 55% by weight or more and 70% by weight or less of styrene monomer units, from the viewpoint of improving the heat resistance and moldability of the resin composition. The constituent units of the AAS copolymer are more preferably 15% by weight or more and 25% by weight or less of acrylonitrile monomer units, 15% by weight or more and 25% by weight or less of acrylic acid ester monomer units, and 60% by weight or more and 65% by weight or less of styrene monomer units, from the viewpoint of improving the heat resistance and moldability of the resin composition.
[0035] 6. Molded products The resin composition can be molded by a known method, such as injection molding, sheet extrusion molding, vacuum molding, blow molding, foam molding, irregular extrusion molding, etc. Molded products can be used for automobile parts, home appliances, office equipment parts, etc. EXAMPLES
[0036] The present invention will be described more specifically below with reference to examples.
[0037] 1. Preparation of resin composition Various resin compositions were prepared according to the blending ratios shown in Table 1-2. In Table 1-2, the details of the main raw materials are shown below. Polycarbonate resin (1): Lupilon (registered trademark) S-1000 manufactured by Mitsubishi Engineering Plastics Corporation Weight average molecular weight Mw: 25,000 to 26,000 MVR measured according to ISO1183: 7.1 Polycarbonate resin (2): Lupilon (registered trademark) S-2000 manufactured by Mitsubishi Engineering Plastics Corporation Weight average molecular weight Mw: 23,000 to 24,000 MVR measured according to ISO1183: 9.0 Polycarbonate resin (3): Lupilon (registered trademark) H-3000 manufactured by Mitsubishi Engineering Plastics Corporation Weight average molecular weight Mw: 18,000 to 19,000 MVR measured according to ISO1183: 28 ABS resin (1): Clarastic (registered trademark) SRE manufactured by Nippon A&L Co., Ltd., MVR measured according to ISO1133: 7.0 (220°C, 10 kg), manufacturing method: emulsion polymerization method ABS resin (2): Clarastic (registered trademark) ET-70 manufactured by Nippon A&L Co., Ltd., MVR measured according to ISO1133: 9.0 (220°C, 10 kg), manufacturing method: continuous bulk polymerization method PMI copolymer: Denka IP (registered trademark) IPX-74 manufactured by Denka Co., Ltd., MVR measured according to ISO1133: 7.0 (240°C, 10 kg), glass transition temperature (Tg): 177°C (DSC method) AAS copolymer: Unibright (registered trademark) UA-1500 manufactured by Nippon A&L Co., Ltd., MVR measured according to ISO1133: 11.0 Specifically, the raw materials for the resin compositions of Examples 1 to 12 and Comparative Example 1 were determined as follows.
[0038] [Table 1]
[0039] [Table 2]
[0040] <Example 1-3> In Example 1-3, polycarbonate resin, ABS resin, PMI copolymer, and AAS copolymer were used as raw materials. In Example 1-3, polycarbonate resins (1) to (3) were used as the polycarbonate resin in the blending ratio shown in Table 1. In Example 1-3, ABS resin (2) produced by continuous bulk polymerization was used as the ABS resin.
[0041] <Example 4-12> In Example 4-12, polycarbonate resin, ABS resin, and PMI copolymer were used as raw materials. In Example 4-12, polycarbonate resins (1) to (3) were used as the polycarbonate resin in the blending ratio shown in Table 1. In Example 4-11, ABS resin (2) produced by continuous bulk polymerization was used as the ABS resin. In Example 12, ABS resin (1) produced by emulsion polymerization was used as the ABS resin.
[0042] <Comparative Example 1> In Comparative Example 1, polycarbonate resin and ABS resin were used as raw materials. In Comparative Example 1, polycarbonate resins (2) and (3) were used as the polycarbonate resin in the blending ratio shown in Table 1. In Comparative Example 1, ABS resin (2) produced by continuous bulk polymerization was used as the ABS resin.
[0043] 2. Evaluation method (1) Heat resistance evaluation Heat resistance was evaluated by measuring the deflection temperature under load according to ISO 75-1. Using the Flatwise A method (load 1.80 MPa), a test piece measuring 4 mm x 10 mm x 80 mm was heated at a starting temperature of 23.0°C and a heating rate of 120.0°C / h, and the temperature (heat distortion temperature) was measured when the deflection reached the standard deflection (0.34 mm).
[0044] (2) Formability evaluation The appearance of the molded articles (test pieces) molded from each of the resin compositions of Examples 1-12 and Comparative Example 1 was evaluated. For each of the resin compositions of Examples 1-12 and Comparative Example 1, 20 molded articles each having a length of 12 cm, a width of 10 cm, a thickness of 3 mm, and a tip with a 30° inclined shape were produced by one-point gate injection using an injection molding machine (FANUC S-2000i100A) under molding conditions of a cylinder temperature of 260° C., a mold temperature of 60° C., and an injection speed of 80 mm / s. The number of samples with appearance defects such as surface peeling and flow marks around the gate and within a range of 5 cm directly below the gate in the molded article was counted, and the appearance was evaluated. In Table 1-2, the A, B, and C in the molding appearance column are as follows: <Molding appearance (condition of molded product)> A: The number of samples with poor appearance (surface peeling, flow marks, etc.) was 0 B: 1 to 2 samples with poor appearance (surface peeling, flow marks, etc.) C: The number of samples with poor appearance (surface peeling, flow marks, etc.) is 3 or more.
[0045] (3) Paintability evaluation The paintability was evaluated for the molded products obtained by molding each of the resin compositions of Examples 1-12 and Comparative Example 1. As in the above (2) moldability evaluation, molded products (test pieces) were prepared by molding each of the resin compositions of Examples 1-12 and Comparative Example 1. Each molded product was left in a temperature-controlled room at room temperature of 23°C and a relative humidity of 50% for 24 hours to adjust its condition. The front surface of each molded product was spray-painted with a color base paint of an acrylic base agent so that the paint thickness was 20μm to 30μm, and left at room temperature for 10 minutes. Next, spray-painted with a paint consisting of an acrylic polyol base agent, an isocyanate curing agent, and a thinner so that the paint thickness was 30μm to 40μm, and dried at 80°C for 30 minutes to obtain a painted test piece. In Table 1-2, the A, B, and C in the paintability column are as follows: <Paintability (condition of painted test piece)> A: No crazing occurs near the injection gate of the coated test piece, and there are no cracks at the tip (slope) corner. B: A thin crazing of 5 mm or less occurs near the injection gate of the coated test piece, and there is no wobble at the tip (slope) corner. C: Thin crazing of 5 mm or more occurred near the injection gate of the coated test piece, or popping occurred at the tip (slope) corner.
[0046] 3. Evaluation results (1) Fulfillment of each requirement in Examples 1-12 The resin compositions of Examples 1-3 satisfy all of the following requirements (a)-(d), and the resin compositions of Examples 4-12 satisfy all of the following requirements (a)-(c). · Requirement (a): Contains polycarbonate resin. · Requirement (b): Contains ABS resin. · Requirement (c): Contains PMI copolymer. · Requirement (d): Contains AAS copolymer. (2) Fulfillment of each requirement in Comparative Example 1 The resin composition of Comparative Example 1 does not satisfy the above requirements (c) and (d).
[0047] (3) Results and Discussion The resin compositions of Examples 1-12 had heat distortion temperatures (temperatures at which the amount of deflection reached the standard amount of deflection (0.34 mm)) of 103°C to 110°C. The resin composition of Comparative Example 1 had a heat distortion temperature of 98°C. It is believed that the resin compositions of Examples 1-12 had improved heat resistance by satisfying the above requirement (c) (containing a PMI copolymer). The resin compositions of Examples 1-12 were evaluated for molded appearance as A or B. The resin composition of Comparative Example 1 was evaluated for molded appearance as C. It is believed that the resin compositions of Examples 1-12 had improved moldability by satisfying the above requirement (c) (containing a PMI copolymer). The resin compositions of Examples 1-12 were evaluated for coatability as A or B. The resin composition of Comparative Example 1 was evaluated for coatability as C. It is believed that the resin compositions of Examples 1-12 had improved coatability by satisfying the above requirement (c) (containing a PMI copolymer). The resin composition of Example 1-3 was evaluated as an A in terms of molded appearance and paintability. The resin composition of Example 4-12 was evaluated as a B in terms of molded appearance and paintability. It is considered that the resin composition of Example 1-3 satisfies the above requirement (d) (contains an AAS copolymer), and thus has further improved moldability and paintability. The resin composition of Examples 1-11, which used the ABS resin produced by the continuous bulk polymerization method, and the resin composition of Example 12, which used the ABS resin produced by the emulsion polymerization method, both had improved heat resistance, moldability, and paintability compared to the resin composition of Comparative Example 1.
[0048] 4. Effects of the embodiment According to the above examples, the resin composition has improved heat resistance, moldability, and paintability. According to the examples, even if a molded article is produced by injection molding, which tends to cause residual distortion, and then the molded article is painted, the occurrence of painting defects such as crazing and popping is suppressed, and a painted molded article having a good appearance can be provided.
[0049] The present disclosure is not limited to the above-described embodiments, and various modifications and variations are possible.
Claims
[Claim 1] Polycarbonate resin; ABS resin, Styrene-N-phenylmaleimide-maleic anhydride-acrylonitrile copolymer; an acrylonitrile-acrylate-styrene copolymer; Including, The constituent units of the styrene-N-phenylmaleimide-maleic anhydride-acrylonitrile copolymer are, when the total of the monomer units is taken as 100% by weight, 30% by weight or more and 70% by weight or less of styrene monomer units, 25% by weight or more and 50% by weight or less of N-phenylmaleimide monomer units, 0.1% by weight or more and 25% by weight or less of maleic anhydride monomer units, and 0.1% by weight or more and 40% by weight or less of acrylonitrile monomer units, The content of the polycarbonate resin is 40 parts by mass or more and 70 parts by mass or less, The content of the ABS resin is 25 parts by mass or more and 40 parts by mass or less, The content of the styrene-N-phenylmaleimide-maleic anhydride-acrylonitrile copolymer is 3 parts by mass or more and 20 parts by mass or less, The content of the acrylonitrile-acrylic acid ester-styrene copolymer is 1 part by mass or more and 10 parts by mass or less.
Citation Information
Patent Citations
Flame-retartdant resin composition
JP1997067512A
Thermoplastic resin composition
JP1997316317A
Copolymer for improving elongation and shock resistance of PC / ABS based resin, and resin composition including copolymer and PC / ABS based resin
JP2015131867A
Resin composition for coating and molded article
JP2019019238A
Thermoplastic resin composition and molded article thereof
WO2020217687A1